Histopathological effects of cypermethrin and Bacillus thuringiensis var. israelensis on midgut of Chironomus calligraphus larvae (Diptera: Chironomidae) - Lavarias, Sabrina Maria Luisa (2017)
Pesticides are extensively used for the control of agricultural pests and disease vectors, but they also affect non-target organisms. Cypermethrin (CYP) is a synthetic pyrethroid used worldwide. Otherwise, bioinsecticides like Bacillus thuringiensis var. israelensis (Bti) have received great attention as an environmentally benign and desirable alternative. In order to evaluate the toxicity of those pesticides, Chironomus calligraphus was selected due to its high sensitivity to some toxicants. Third and fourth instars larvae were exposed to serial dilutions of CYP and Bti to determine LC50 values. In order to evaluate the potentially histopathological alterations as biomarkers, after 96-h of exposure, live larvae were fixed for histological analysis of the mid region of digestive tract. The 96-h LC50 values were 0.52 and 1.506 μg/L for CYP and Bti, respectively. Midgut histological structure of the control group showed a single layer of cubical cells with microvilli in their apical surface and a big central nucleus. The midgut epithelium of larvae exposed to a low concentration of CYP (0.037 μg/L) showed secretion activity and vacuolization while at high concentration (0.3 μg/L) cells showed a greater disorganization and a more developed fat body. On the other hand, Bti caused progressive histological damage in this tissue. Chironomus calligraphus is sensitive to Bti and CYP toxicity like other Chironomus species. The histopathological alterations could be a valuable tool to assess toxicity mechanism of different pesticides.